2020
DOI: 10.1016/j.heliyon.2020.e03351
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating cytotoxicity of methyl benzoate in vitro

Abstract: Methyl benzoate (MB) is a small, hydrophobic organic compound that is isolated from the freshwater fern, Salvinia molesta. Because of its pleasant odor, it has been used as a fragrance and flavor enhancer. In addition, it is used to attract orchid bees for pollination in the farm and has been tested for its potential to be developed as a green pesticide targeting a diverse group of insects. In spite of its wide applications, the safety of MB to humans remains poorly understood. In this study, we tested the cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Strikingly, AS6 altered the transcription of a large number of genes in MCF7 cells whereas much fewer genes were RNA-seq. Cell culture and RNA preparation were performed as described in 32 . HUMEC and MCF7 cells were grown to 60-70% confluence in 6-well plates and the media were exchanged with the fresh complete media including AS6 at final concentration of 0.5 µM or H 2 O only as an untreated control.…”
mentioning
confidence: 99%
“…Strikingly, AS6 altered the transcription of a large number of genes in MCF7 cells whereas much fewer genes were RNA-seq. Cell culture and RNA preparation were performed as described in 32 . HUMEC and MCF7 cells were grown to 60-70% confluence in 6-well plates and the media were exchanged with the fresh complete media including AS6 at final concentration of 0.5 µM or H 2 O only as an untreated control.…”
mentioning
confidence: 99%
“…Recently a number of studies have reported gene regulation by small environmental chemicals, both natural and synthetic [ 23 , 24 , 32 , 33 ]. In a previous study, vinyl benzoate, a synthetic, hydrophobic compound with a notable cytotoxicity (LC 50 = 0.08% in HEK293), showed a marked reduction in HSP70 expression in both RNA and protein levels [ 24 ]. HSP70 is a chaperon protein, which is critical for responses to various stresses in the cell, including heat, osmatic, chemical, and physical stresses.…”
Section: Resultsmentioning
confidence: 99%
“…Lignin was precipitated by acidifying with sulfuric acid from the organosolv black liquor. To evaluate the cytotoxicity of L-MFC, we performed a water-soluble tetrazolium salt (WST) assay using human kidney and lung cell lines, HEK293 and H460, respectively [ 23 , 24 ]. The cytotoxicity of L-MFC was compared to those of lignin and cellulose, and the susceptibility and LC 50 values of L-MFC for the cells were monitored and measured.…”
Section: Introductionmentioning
confidence: 99%
“…Cell culture and RNA preparation were performed as described in [32]. HUMEC and MCF7 cells were grown to 60-70% confluence in 6-well plates and the media were exchanged with the fresh complete media including AS6 at final concentration of 0.5 µM or H 2 O only as an untreated control.…”
Section: Methodsmentioning
confidence: 99%